A Precarious Path to Partnership? The Moderating Effects of Labour Market Regulations on the Relationship Between Unstable Employment and Union Formation in Europe - Chen-Hao Hsu; Henriette Engelhardt (European Journal of Population, 2024)
Rising employment uncertainty featured by higher risks of being temporarily employed or unemployed is often seen as the driving force behind delayed and declined partnering in Western countries. However, such an employment–partnering relationship is contextualized by labour market institutions and thus could diverge across countries over time. This paper aims to investigate how country-level variations in labour market regulations moderate individual-level effects of unstable employment on union formation, including the transitions into marriage or cohabitation unions. Using comparative panel data for 26 countries from the European Union Statistics on Income and Living Conditions (the years 2010–2019), our multilevel fixed effects models showed that temporary employment and unemployment negatively affected the probability of union formation for single women and men in Europe. Moreover, the negative relationship between unstable employment and union formation was reinforced when labour market reforms were stimulating insider–outsider segregations or decreasing welfare provisions. Specifically, stricter employment protection legislations and higher coverage rates of collective bargaining agreements could reinforce the negative effects of temporary employment and unemployment on union formation, while more generous provisions of unemployment benefits could buffer such negative effects.
Keywords: 300; Union formation; Unstable employment; Labour market regulations; Institutions; Multilevel analysis; Country fixed effects models